Performance Optimization of Unit I Resume Satreskrim Polresta Surakarta to Enhance the Crime Clearance Rate of Vehicle Theft Crime - Sutijono, Breggy Yesaya Imanuel (Indonesian Journal of Police Studies, 2024)
Thesis raises the performance of Unit I Resum Satreskrim Polresta Surakarta in order to enhance the crime clearance rate of vehicle theft. The vehicle theft is the most frequent crime in Surakarta. To support the analysis, this thesis uses the theory of performance, Balanced Scorecard, and SWOT theory. The role of the theories is used to analyze the problem solving of vehicle theft investigation. This thesis uses field research in qualitative method. Interview, observation, and documents are the methods used in data collection. The result of this thesis shows the performance of Unit I Resum is not optimal and followed by the crime clearance rate of vehicle theft. The performance of Unit I indicates disparity between the factual condition and the regulations. The problem problem solving are analyzed according to the phenomenon in first line supervisor.